PENERAPAN THINK PAIR SHARE SEBAGAI UPAYA MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR - Mendrofa, Yusdiani (JURNAL PENA EDUKASI, 2018)
Abstract: The purpose of this study was to improve: (1) the activeness of students of Class IX-B of SMP Negeri 5 Gunungsitoli in participating in Integrated Economics subjects, especially Economics through TPS cooperative learning model, (2) the achievement of students of Class IX-B SMP Negeri 5 Gunungsitoli in following the eyes Integrated Social Studies lessons especially Economics through TPS cooperative learning models. This study uses a classroom action research approach. The subjects of this study were Class IX-B students of SMP Negeri 5 Gunungsitoli, amounting to 40 students. This research was carried out in collaboration between researchers, social studies teacher colleagues and involved student participation. Data collection techniques are carried out through activities in the form of: (a) observation, (b) interviews, (c) tests. Research procedures include stages: (a) action planning, (b) implementation of actions, (c) observation and interpretation, and (d) analysis and reflection. Based on the results of the study it can be concluded: (1) the application of the TPS cooperative learning model can improve student activity during learning. (2) the application of the TPS cooperative learning model can improve student learning achievement. Keywords: Think Pair Share, Learning Achievement Abstrak: Tujuan penelitian ini adalah untuk meningkatkan : (1) keaktifan siswa Kelas IX- B SMP Negeri 5 Gunungsitoli dalam mengikuti mata pelajaran IPS Terpadu khususnya Ekonomi melalui model pembelajaran kooperatif TPS, (2) prestasi siswa Kelas IX- B SMP Negeri 5 Gunungsitoli dalam mengikuti mata pelajaran IPS Terpadu khususnya Ekonomi melalui model pembelajaran kooperatif TPS. Penelitian ini menggunakan pendekatan penelitian tindakan kelas. Subyek penelitian ini adalah siswa Kelas IX- B SMP Negeri 5 Gunungsitoli yang berjumlah 40 siswa. Penelitian ini dilaksanakan dengan kolaborasi antara peneliti, rekan guru IPS dan melibatkan partisipasi siswa. Teknik pengumpulan data dilakukan melalui kegiatan berupa : (a) observasi, (b) wawancara, (c) tes. Prosedur penelitian meliputi tahap : (a) perencanaan tindakan, (b) pelaksanaan tindakan, (c) observasi dan interprestasi, dan (d) analisis dan refleksi. Berdasarkan hasil penelitian dapat disimpulkan: (1) penerapan model pembelajaran kooperatif TPS dapat meningkatkan keaktifan siswa selama pembelajaran. (2) penerapan model pembelajaran kooperatif TPS dapat meningkatkan prestasi belajar siswa. Kata kunci: Think Pair Share, hasil Belajar